Pressure stability of lipases and their use in different systems - Knez, Željko; Leitgeb, Maja (Slovensko kemijsko društvo, 2015)
For the investigation of the solvent impact on the enzymes, lipases from different sources (Pseudomonas fluorescences, Rhizopus javanicus, Rhizopus niveus, Candida rugose and Porcine pancreas) were used. Stability and activity of these lipases in aqueous medium in supercritical $CO_2$ and liquid propane at 100 bar and 40°C were studied. On the basis of previous results lipases were used for their application in two different systems. The application of the polysulphone membrane in the continuous stirred tank membrane reactor was studied on the model system of the hydrolysis of oleyl oleate in propane at high pressure. As a catalyst the Candida rugosa lipase was used. The next utilization of lipases was the use of on silica arerogel self-immobilized lipase from Porcine pancreas as catalyst for esterification reaction in near-critical propane at 40°C and 100 bar. Za študijo vpliva topil na encime smo izbrali lipaze iz raznih virov (Pseudomonas fluorescences, Rhizopus javanicus, Rhizopus niveus, Candida rugosa in Prochine pancreas). Ugotavljali smo spremembe v aktivnosti oz. stabilnosti omenjenih lipaz v vodnem mediju pri atmosferskem tlaku, v superkritičnem $CO_2$ in sub-kritičnem propanu. Na osnovi dobljenih rezultatov smo lipaze uporabili kot katalizatorje v dveh različnih sistemih. Uporabo polisulfonskih membran v kontinuiranem mešalnem membranskem reaktorju smo študirali s pomočjo modelnega sistema hidrolize oleil oleata v sub-kritičnem propanu. Kot katalizator smo uporabili lipazo iz candida rugose. Druga aplikacija pa je bila uporaba Porchine pancreas lipaze, ki smo jo predhodno sami imobilizirali na silicijevem aerogelu, za katalizo esterifikacije v sub-kritičnem propanu.